International clinical assessment of smell: An international, cross-sectional survey of current practice in the assessment of olfaction - Whitcroft, Katherine L; Alobid, Isam; Altundag, Aytug; Andrews, Peter; Carrie, Sean; Fahmy, Miriam; Fjaeldstad, Alexander W; Gane, Simon; Hopkins, Claire; Hsieh, Julien Wen; Huart, Caroline; Hummel, Thomas; et al. (Wiley-Blackwell, 2023)
Objectives: Olfactory dysfunction (OD) is common and carries significant personal and societal burden. Accurate assessment is necessary for good clinical and research practice but is highly dependent on the assessment technique used. Current practice with regards to UK/international clinical assessment is unknown. We aimed to capture current clinical practice, with reference to contemporaneously available guidelines. We further aimed to compare UK to international practice.DesignAnonymous online questionnaire with cross-sectional non-probability sampling. Subgroup analysis according to subspeciality training in rhinology ('rhinologists' and 'non-rhinologists') was performed, with geographical comparisons only made according to subgroup.ParticipantsENT surgeons who assess olfaction.ResultsResponses were received from 465 clinicians (217 from UK and 17 countries total). Country-specific response rate varied, with the lowest rate being obtained from Japan (1.4%) and highest from Greece (72.5%). Most UK clinicians do not perform psychophysical smell testing during any of the presented clinical scenarios-though rhinologists did so more often than non-rhinologists. The most frequent barriers to testing related to service provision (e.g., time/funding limitations). Whilst there was variability in practice, in general, international respondents performed psychophysical testing more frequently than those from the UK. Approximately 3/4 of all respondents said they would like to receive training in psychophysical smell testing. Patient reported outcome measures were infrequently used in the UK/internationally. More UK respondents performed diagnostic MRI scanning than international respondents.ConclusionsTo our knowledge, this is the most comprehensive UK-based, and only international survey of clinical practice in the assessment of OD. We present recommendations to improve practice, including increased education and funding for psychophysical smell testing. We hope this will promote accurate and reliable olfactory assessment, as is the accepted standard in other sensory systems.
Mezinárodní klinické hodnocení čichu: Mezinárodní průřezový průzkum současné praxe v hodnocení čichu
Keywords: assessment; clinical practice; international; olfactory dysfunction; UK; vyšetření; klinická praxe; mezinárodní; poruchy čichu; UK